2002
DOI: 10.1038/sj.ejcn.1601440
|View full text |Cite
|
Sign up to set email alerts
|

Family resemblance in breakfast energy intake: the Stanislas Family Study

Abstract: Background: There seems to be a consensus that family influences on dietary habits are important. However, no data relative to breakfast have been published yet. Objective: To investigate whether and how breakfast energy intake aggregates within French families. Design: A total of 398 families of the Stanislas Family Study who filled in a 3 day food consumption diary were selected. Absolute and relative breakfast energy intakes (BEI in kcal=day and RBEI in percentage of daily intake, respectively) were both st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
(43 reference statements)
2
14
0
1
Order By: Relevance
“…There has also been proposed a hypothesis that frequent snacking might improve appetite control and increase dietary-induced thermo genesis [27]. However, eating regular meals may prevent the snacking of energy-dense unhealthy foods between meals [14] and the ZENDOS study among Swedish adults reported that frequent snacking might be associated with obesity [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has also been proposed a hypothesis that frequent snacking might improve appetite control and increase dietary-induced thermo genesis [27]. However, eating regular meals may prevent the snacking of energy-dense unhealthy foods between meals [14] and the ZENDOS study among Swedish adults reported that frequent snacking might be associated with obesity [28].…”
Section: Discussionmentioning
confidence: 99%
“…Eating regular meals may prevent snacking of energy dense unhealthy foods between meals [14]. The reduced thermic effect of food after irregular meal frequencies may lead to weight gain in the long term [15].…”
Section: Introductionmentioning
confidence: 99%
“…The Stanislas Study (9,99) Longitudinal survey involving 1006 families recruited during a free health check-up at the Center for Preventive Medicine in Nancy (France) between 1994 and 1995. The families underwent a free health check-up every 5 years.…”
Section: Wwwannualreviewsorg • Family History In Public Health Pracmentioning
confidence: 99%
“…(1) Among youth, one in three aged [6][7][8][9][10][11][12][13][14][15][16][17][18][19] years is overweight (>85 th percentile) and one in six aged 6-19 is obese (>95 th percentile). (1) Among behaviors related to obesity, television viewing, eating while watching television, and consuming soda/sugar-sweetened beverage have been shown as obesity risk factors.…”
Section: Introductionmentioning
confidence: 99%